The Influence of Self-Regulation, Resilience, and Family Environment on Mathematics Learning Outcomes of Junior High School Students in Serang City, Indonesia - Nabilah, Syifa; Syamsuri, Syamsuri; Pujiastuti, Heni (International Journal of STEM Education for Sustainability, 2024)
This study aimed to identify and analyze self-regulation that mediates the influence of resilience and family environment on students' mathematics learning outcomes. This descriptive research uses the method of explanatory survey with a quantitative approach. The variables in this study were mathematics learning outcomes (Y), resilience (X1), family environment (X2), and self-regulation (Z). Learning outcomes are the dependent variable (endogenous variable). At the same time, resilience and family environment are independent variables (exogenous variable), and self-regulation is a mediating variable (intervening variable) with questionnaires and observations to collect data. This study's population was all class VII students at State Middle School in Serang City, while the sample was randomly selected from as many as 332 students. The collected data is then analyzed using a structural equation model. The results of this study indicate that (i) there is a significant effect of resilience on mathematics learning outcomes, (ii) there is a significant effect of the family environment on student learning outcomes, (iii) there is a significant effect of self-regulation ability on mathematics learning outcomes (iv) there is a significant effect of resilience on students' abilities self-regulation (v) there is a significant influence of the family environment on self-regulation abilities (vi) there is a significant effect of resilience on student learning outcomes through self-regulation abilities (vii) there is a significant influence of the family environment on student learning outcomes through self-regulation abilities (viii) there is a significant influence resilience, family environment, and ability to self-regulate on mathematics learning outcomes. The results of this study imply that the concepts of resilience, family environment, and self-regulation are relevant and can estimate student learning outcomes.